2015
DOI: 10.1227/neu.0000000000000586
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ruptured Intracranial Aneurysms With the Pipeline Embolization Device

Abstract: In our preliminary experience, treatment of ruptured aneurysms with the PED was associated with low complication rates, high occlusion rates, and favorable outcomes. These findings suggest that PED may be a safe and effective option for patients with favorable Hunt and Hess grades and aneurysms difficult to treat with conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…15 A procedure-related complication was seen in only 1 patient, who experienced an acute aneurysm rerupture, leading to her death. The occlusion rate was 80%, and 95% of patients had a favorable outcome (mRS score of 0-2) at most recent follow-up.…”
mentioning
confidence: 97%
“…15 A procedure-related complication was seen in only 1 patient, who experienced an acute aneurysm rerupture, leading to her death. The occlusion rate was 80%, and 95% of patients had a favorable outcome (mRS score of 0-2) at most recent follow-up.…”
mentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Reports in the literature, however, are conflicting concerning the optimal strategy in using this new device. 1,2,4,13,15,16,[18][19][20][21] The addition of coil embolization to flow diversion, while prevalent in daily use, has not been subjected to a large systematic analysis. [7][8][9][10][11]16,[21][22][23][24] The earliest case report hypothesized that coils within the aneurysm sac can augment the degree of flow diversion with the goal of improved occlusion of the aneurysm.…”
mentioning
confidence: 99%
“…1,2,4,13,15,16,[18][19][20][21] The addition of coil embolization to flow diversion, while prevalent in daily use, has not been subjected to a large systematic analysis. [7][8][9][10][11]16,[21][22][23][24] The earliest case report hypothesized that coils within the aneurysm sac can augment the degree of flow diversion with the goal of improved occlusion of the aneurysm. 1 Others believe that adjunctive coil embolization does little to improve the already high occlusion rates obtained by using the Pipeline Embolization Device (PED; Covidien, Irvine, California) alone.…”
mentioning
confidence: 99%
“…Over 90% of patients had good neurological and angiographic outcomes in this study. 2 McAuliffe et al reported a series of 11 acutely ruptured aneurysms treated with the PED within 1 month of rupture. Of these aneurysms, 6 received concomitant coiling.…”
Section: Discussionmentioning
confidence: 99%